1998
DOI: 10.1007/pl00005261
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine interacts with the noradrenaline transporter at a site partly overlapping the desipramine binding site

Abstract: Effects of the intravenous anaesthetic ketamine on the desipramine-sensitive noradrenaline transporter (NAT) were examined in cultured bovine adrenal medullary cells and in transfected Xenopus laevis oocytes expressing the bovine NAT (bNAT). Incubation (1-3 h) of adrenal medullary cells with ketamine (10-300 microM) caused an increase in appearance of catecholamines in culture medium. Ketamine (10-1000 microM) inhibited desipramine-sensitive uptake of [3H]noradrenaline (NA) (IC50=97 microM). Saturation analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…In particular, sympathomimetic effects of ketamine have been shown to be due to inhibition of the noradrenaline (NA) transporter system. A number of investigators have reported that ketamine suppresses [ 3 H]NA uptake in various sympathetic nervous tissues (Taube et al 1975;Azzaro and Smith 1977;Garty et al 1990;Graf et al 1995) and the adrenal medulla (Hara et al 1998). All previous reports described acute effects of ketamine on noradrenaline transporter (NAT) activity.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In particular, sympathomimetic effects of ketamine have been shown to be due to inhibition of the noradrenaline (NA) transporter system. A number of investigators have reported that ketamine suppresses [ 3 H]NA uptake in various sympathetic nervous tissues (Taube et al 1975;Azzaro and Smith 1977;Garty et al 1990;Graf et al 1995) and the adrenal medulla (Hara et al 1998). All previous reports described acute effects of ketamine on noradrenaline transporter (NAT) activity.…”
Section: Introductionmentioning
confidence: 95%
“…We have recently reported that ketamine directly interacts with NAT at a site partly overlapping the antidepressant binding site and acutely inhibits its functional activity in bovine adrenal medullary cells (Hara et al 1998). In the present study, we examined the effects of prolonged exposure to ketamine on the functional activity, number, and mRNA of NAT in cultured bovine adrenal medullary cells and demonstrate an up-regulation of NAT in the cells induced by ketamine.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The pharmacological properties of NET in bovine adrenal medullary cells are similar to those of NET in central and peripheral noradrenergic neurons (13). Therefore, NET in bovine adrenal medullary cells has provided a convenient model for studying the effects of various agents such as anesthetics and antipsychotic drugs on this transporter (19,20). Some centrally acting analgesic agents such as tramadol have both opioid and monoamine modes of action (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in systolic and diastolic pressure in animals, as well as in man, is mainly due to enhanced cardiac output (Domino et al, 1965;Virtue et al, 1967;Schwartz & Horwitz, 1975). Moreover, A number of investigators have reported that ketamine suppresses [ 3 H]NA uptake in various sympathetic nervous tissues (Taube et al, 1975;Azzaro & Smith, 1977;Garty et al, 1990;Graf et al, 1995) and the adrenal medulla (Hara et al, 1998;Hara et al, 2002). Local administration of ketamine was also found to induce an increased norepinephrine (NE) levels in dialysate in anesthetized cats (Kitagawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%